2016
DOI: 10.1530/erc-16-0067
|View full text |Cite
|
Sign up to set email alerts
|

Familial non-medullary thyroid cancer: unraveling the genetic maze

Abstract: Familial non-medullary thyroid cancer (FNMTC) constitutes 3-9% of all thyroid cancers. Out of all FNMTC cases, only 5% in the syndromic form has well-studied driver germline mutations. These associated syndromes include Cowden syndrome, familial adenomatous polyposis, Gardner syndrome, Carney complex type 1, Werner syndrome and DICER1 syndrome. It is important for the clinician to recognize these phenotypes so that genetic counseling and testing can be initiated to enable surveillance for associated malignanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 120 publications
(162 reference statements)
0
57
0
4
Order By: Relevance
“…Functional studies have shown the mutant variant increased tumor colony formation and cell migration consistent with the loss of tumor suppressor effect. The HABP2 G534E variant has also been reported in another cohort in the U.S. [106] but not in the Middle Eastern or UK, or Chinese cohorts [102]. The TTF1 germline mutation has been reported in two families with PTC and coexisting multinodular goiter.…”
Section: Familial Non-medullary Thyroid Cancermentioning
confidence: 93%
See 1 more Smart Citation
“…Functional studies have shown the mutant variant increased tumor colony formation and cell migration consistent with the loss of tumor suppressor effect. The HABP2 G534E variant has also been reported in another cohort in the U.S. [106] but not in the Middle Eastern or UK, or Chinese cohorts [102]. The TTF1 germline mutation has been reported in two families with PTC and coexisting multinodular goiter.…”
Section: Familial Non-medullary Thyroid Cancermentioning
confidence: 93%
“…Known familial tumor syndromes that feature thyroid cancer account for only 5% of all familial non-medullary thyroid cancer (FNMTC). These syndromes include familial adenomatous polyposis (Gardner's syndrome), Cowden syndrome, Werner syndrome, Carney complex, and DICER1 mutation syndrome [102]. Much effort to identify susceptibility genes involved in non-syndromic familial thyroid cancer has resulted in the identification of FOXE1, HABP2, and TITF1.…”
Section: Familial Non-medullary Thyroid Cancermentioning
confidence: 99%
“…If the genetic background of DTC is strong, linkage analyses should easily uncover predisposing loci in affected families. However, such linkage analyses have identified only a handful of genes; driver mutations existed in single families and they were absent in sporadic DTC [12]. Therefore, it seems that the genetic predisposition to DTC is probably polygenic with low-penetrance genes involved.…”
Section: Reviewmentioning
confidence: 99%
“…Die Diagnosestellung erfolgt meist im jungen Erwachsenenalter, selten früher oder nach dem 50. LJ [4,22] Bis zu 60 % der Patienten zeigen insbesondere in Kindheit/Adoleszenz eine Schilddrüsenbeteiligung in Form von unspezifischen zystischen Veränderun-gen (75 %), meist follikulären Adenomen (25 %) und selten (<10 %) papillären oder follikulären Karzinomen [19,21].…”
Section: Carney-komplexunclassified